All‐in‐one solid‐phase microextraction: Development of a selective solid‐phase microextraction fiber assembly for the simultaneous and efficient extraction of analytes with different polarities. Issue 9 (12th May 2016) - Gharari, Hossein; Farjaminezhad, Manoochehr; Marefat, Abdolrahim; Fakhari, Ali Reza
Abstract : In the present work, for the first time, an all‐in‐one solid‐phase microextraction technique was developed for the simultaneous and efficient extraction of analytes within a vast polarity range. A novel fiber assembly composed of two different steel components each coated with different coatings (polydimethylsiloxane and polyethylene glycol) in terms of polarity by sol–gel technology was employed for the extraction of model compounds of different polarity in a single run followed by gas chromatography with mass spectrometry. Effective parameters in the extraction step and gas chromatography with mass spectrometry analysis were optimized for all model compounds. The detection limits of the developed method for model compounds were below 0.2 ng/L. The repeatability and reproducibility of the proposed method, explained by relative standard deviation, varied between 7.22 and 9.15% and between 7.95 and 14.90 ( n = 5), respectively. Results showed that, under random conditions, compared to separate extractions performed by two other differently end‐coated components that had not been assembled as the final dual fiber, as two individual fibers; simultaneous, efficient and relatively selective extraction of all model compounds was obtained in a single run by the proposed all‐in‐one technique. Finally, the optimized procedure was applied to extraction and determination of the model compounds in spiked water samples.